ETIKA ISLAM TENTANG PEMBERITAAN POLITIK DI INDONESIA - Joko Tri Haryanto (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
Life of the nation can not be separated from political events in which people participation are required. In determining political attitudes, people need information such as those obtained from political news. But in reform era, freedom of political news is highlighted in its ethical practices. As a Muslim majority country, Islamic ethics becomes an important source for political news in Indonesia. This study is conducted in philosophical method, by way of inventive and heuristic. This article expresses the ethics of political news in a review of Islamic ethics. In the level of text, ethics of reporting politics lays on mass media which should represent politics in its truth, at the level of discourse practice, responsibility and professional ethics are imperative categorical for the actors, at the level of sociocultural practice, the vision of media should be on a just and prosperous society.